TECHNOLOGICAL AGNOSTICISM AND CLIMATE CHANGE: PLATFORM CULTURE ON TECHNOLOGY FORUM WHIRLPOOL - Rodriguez, Aleesha Joy (AoIR Selected Papers of Internet Research, 2021)
This paper explores the (limited) discussion of climate change within energy debates on Australian technology forum Whirlpool. These discussions are characterised by $2 , which is an attitude that no technology is $2 or $2 than any other because different technologies have different applications depending on the requirement. By completing a thematic analysis of all Whirlpool replies within four threads centred on energy debates (n = 3,101), I observed Whirlpool contributors depoliticise energy technologies by removing climate change as a factor when considering technology choices. Overall, I found that when technological agnosticism was expressed within these debates, it intersected with issues concerning the $2 , $2 , $2 , and $2 of technology and pushed against concerns regarding climate change. I argue that the prevalence of technological agnosticism within these debates is not an example of climate change denial per se but a reflection of Whirlpool’s platform culture which valorises traits of $2 such as rationality and neutrality (Massanari, 2017). I conclude by comparing Whirlpool’s platform culture to Reddit and suggest that future research ought to explore how particular platform cultures shape energy debates and ultimately, attitudes and action towards climate change.